Gene structure, evolution and expression analysis of the P-ATPase gene family in Chinese pear (Pyrus bretschneideri). (October 2020) - Manzoor, Muhammad Aamir; Cheng, Xi; Li, Guohui; Su, Xueqiang; Abdullah, Muhammad; Cai, Yongping
Graphical abstract: Highlights: Identified and characterized P-ATPase genes in pear and divided into 4 subfamilies according to phylogenetic analysis. We analyzed the gene structure, chromosomal location and microsynteny analysis in pear. Transcriptome data showed that P-ATPase gene might play an important role in lignin biosynthesis during fruit development. The real-time qRT-PCR analysis showed that all P-ATPase genes were differentially expressed in different tissues. Expression profiles of P-ATPase genes were detected under the exogenous hormonal treatment. Abstract: P-ATPase are a large protein family of integral membrane, playing an important role in plant growth, development and stress. P-ATPase genes family have been identified and characterized in several model plants such as cotton, grapes, tobacco, rice, rubber plant and Arabidopsis. However, still lack of comprehensive study of P-ATPase genes in Chinese pear ( Pyrus bretschneideri ). A systematic analysis was performed and identified 30 P-ATPase genes from the pear genome to evaluate the qualities and diversity of P-ATPase proteins. Phylogenetic analysis was performed using A. thaliana P-ATPase genes as a model, allowing us to categorize into 4 subfamilies ( PbHMA, PbECA, PbACA, and PbAHA ) and two subfamilies (ALA and P5 ) is absent in pear. Even Within the same subclade, P-ATPase genes also shows the similar exon-intron structure and conserved motif structure. Continuing chromosomal localization analysis showed that 23 P-ATPase genes were distributed among 13 chromosome and 7 gene on the scaffold of pear. Promoter regions of P-ATPase genes revealed that several cis -acting elements were involved in plant growth/development, stress responses as well as hormone responses. Additionally, P-ATPase genes were also differentially expressed under hormones treatments of ABA (abscisic acid) and SA (salicylic acid) treatments. Remarkably, the transcriptome data exposed that P-ATPase gene might play an important role in lignin biosynthesis during fruit development. The real time qRT-PCR was performed, and the expression analysis indicated that various P-ATPase genes extremely expressed during different developmental stages of fruit. Our study provides valuable information about the P-ATPase gene family in pear fruit development and lignin polymerization.